Electrochemical immunosensor for detection of cancer biomarkers based on porous graphene - Ng, Kwan Sing (2018)
With the rising population of biosensing-related research, demands for biosensors with superior sensitivity and selectivity are increasing exponentially. Materials with large surface area are able to improve the sensitive current response to a higher level, as it helps to promotes electrons transfer between the electrode and molecules detection. Therefore, graphene is chosen as the material to be used for surface modification of an electrochemical sensor due to its exceptional porous properties, which possess high surface are and high pores volume. These unique properties of graphene show its potential as an ideal material to be used for surface modification of an electrochemical sensor. To test the capability of specific and sensitive detection of Prostate specific antigen (PSA), 3D porous graphene is deposited on Au electrodes, undergoing a series of test, such as enzyme-lined immunosorbent assay (ELISA) and cyclical voltammetry, to assess the effectiveness of the modified electrode. The modified electrode manages to produce results with a surprisingly higher absorbance rate than a normal Au electrode with the immunosorbent assay (ELISA) test and excellent sensitivity with the cyclical voltammetry test with the additional capability of detecting PSA antigen’s concentration in the scale of ng/ml. The data obtained from experimenting of the graphene’s unique properties provides the solid base for the future of the biomedical field in electrochemical biosensor.